Batch simulation of solar cells by using Matlab and wxAMPS - Yiming Liu; Yun Sun; Rockett, Angus (2012 38th IEEE Photovoltaic Specialists Conference, 2012)
In this work we present a versatile simulation tool for the batch processing of solar cell simulation by using Matlab and the wxAMPS console version. The wxAMPS console version gives a programming interface for other software to call the simulation kernel of wxAMPS, and Matlab provides a favorable platform to define the modeling process and design the data visualization. This method offers users a full flexibility to develop modeling routines and systems specific to the research subjects or characterization methods, and helps on carrying out a bunch of simulation to implement systematical analysis on solar cells. Besides performing traditional solar cell modeling, this method is also capable of integrating advanced optimization algorithms from the computer science to the development of solar cells.